Wandel durch Handel im neuen Systemwettbewerb – Zeit für eine Truman-Doktrin 2.0? - Erdal Yalçin (Wirtschaftsdienst, 2024)
This article analyses the development and challenges of international trade as a means of economic and political transformation. It examines the historical role of free trade in global integration and highlights the growing criticism of its effectiveness in the face of rising authoritarian regimes. The article underscores the necessity of political support for trade, as exemplified by the Truman Doctrine, and hypothesises that international trade, without accompanying political measures and institutional support, cannot achieve sustainable economic and political transformations.
Keywords: F13; F50; F53; O19; 330